PERLINDUNGAN HUKUM KONSUMEN PENGGUNA JASA LAYANAN INTERNET DITINJAU DARI UNDANG – UNDANG TENTANG PERLINDUNGAN KONSUMEN - Mario, Firman; Hendri Jayadi; Mangisi Simanjuntak (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
In the current era of globalization, the internet is very important and strategic in human life. Human needs on the internet are getting higher to carry out daily activities such as communicating and obtaining information. The formulation of the problem in this writing is how is the legal protection for consumers who use internet service providers in terms of Law No. 8 of 1999 concerning Consumer Protection and what is the responsibility of internet service provider business actors to consumers in the event of network disruption in terms of law. This study uses the normative juridical law research method, namely library law research, namely research on primary data, which is studied, namely the rules written in primary legal material, namely laws, norms, or other rules, while secondary legal material is obtained from books. – books, journals and other literature. From the results of this study, it can be interpreted that legal protection for users of internet service providers does not yet have certainty that can and legal accountability is carried out by Business Actors for internet provider services is still not optimal because consumers often experience problems in using the internet network and fulfilling rights that are still need to be considered by consumers.